DETERMINAN TURNOVER INTENTIONS DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Kasus Kantor Konsultan Pajak di Semarang) (Students' Journal of Accounting and Banking, 2013)
The research was aimed to examine the effect of role conflict, professional commitment, and job satisfaction to turnover intentions. The theory used is the Theory of Reasoned Action. This theory reveals the background or reason of an act. High employee turnover intentions caused as the unreached target, the instructions or commands that are not clear, and the inconvenience of doing the work. The discomfort in the work since triggered a conflict can lead to a sense of dissatisfaction even to leave the job.Sample was selected by judgment sampling technique for 54 respondents working in tax consulting firm and the employees are graduates of accounting. This data is tested with the validity, reliability, normality, multicollinearity, heteroscedasticity, and path analysis. The results of the test showed that it is avoided from breach of data quality and classical assumptions. Further analysis the researcher used multiple linear regression to describe the relationship between variables.The results obtained are role conflict has no effect on job satisfaction, professional commitment has significant positive effect on job satisfaction. Role conflict has significant positive effect on turnover intentions. Professional commitment and job satisfaction has significant negative effect on turnover intentions. Job satisfaction has not been proven as an intervening variable so that is no indirect effect between role conflict and professional commitment on turnover intentions.Keywords: Role Conflict, Professional Commitment, Job Satisfaction, Turnover Intentions.